Evaluation of Medix Hospital System on Record Management at E-med Healthcare Solution: Basis for Improvement: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The digital era has made life easier and faster, but there is an opposing viewpoint thattechnology can be destructive to humans. Records Management (RM) and ElectronicRecords Management (ERM) are two activities that have been shown to be advantageous inthe workplace. Record Management (RM) oversees the effective and systematic control ofthe creation, receipt, maintenance, use, and disposition of records, while ERM oversees theeffective and systematic control of the creation, receipt, maintenance, use, and disposition ofrecords. Records management is an essential task that enhances a company and can bepart of its culture. E-Med Healthcare Solutions Incorporated is one of the companies focusedon exceeding their client's expectations by providing excellent products, outstandingcustomer support service, greater value, and increased flexibility.The accuracy of records showed that all information about each patient was true andprecisely recorded in the system, while e-med Healthcare Solutions Inc. integrated recordmanagement as part of daily operations. The processing of data in the Medix informationsystem demonstrated how well the system functions and the sending and receiving of datademonstrated how quickly and accurately the system offers accurate information and canhandle large files. The system is office-friendly and secure against data loss, but the systemsoftware is not updated.The questionnaire was given to the employees and created effective and practicalquestionnaires with the help of grammarians and statisticians. The program offers a securemethod of filing, the respondents are sure that their software offers accurate records, andthe existing software is working effectively and at the top of its office-friendly performance.Moreover, they must prioritize updating their system. The system they are using is outdated,which could damage the staff's trust in their ability to compete. On the other hand,innovations are rapidly expanding today.
Keywords: Business Administration